EFEKTIVITAS KETERLIBATAN PIHAK SWASTA DALAM PROSES PENGANGKUTAN SAMPAH DI KOTA PEKANBARU - Lisa Indah Ramadayanti; Geovani Meiwanda (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
To achieve waste tonnage in waste transportation in the city of Pekanbaru, the government of the Environmental and Hygiene Service has made a waste privatization policy that has been carried out since 2015. PT Godang Tua Jaya and PT Samhana Indah, which are third parties, are tasked with transporting waste. The collaboration carried out in the privatization of waste is going well, so that the tonnage curve of waste in waste transportation continues to increase. This study aims to determine the process and supporting factors in Collaboration between Actor in Waste Management in Zones 1 and 2 in Pekanbaru City. This study uses a qualitative approach with descriptive data. The results showed that first, the collaboration process between actors in waste management in zones 1 and 2 went well according to cooperation, assertiveness, responsibility, communication, coordination and mutual respect and trust. Second, There are two factors influencing the collaboration between actors in waste management in zones 1 and 2 in Pekanbaru city. First, the supporting factors that encourage collaboration between actors in waste management in zones 1 and 2 in Pekanbaru city, including budget, availability of facilities and infrastructure, and community participation. The two inhibiting factors that become collaboration between actors in waste management in zones 1 and 2 in the city of Pekanbaru, namely the existence of independent waste transportation, thus hindering collaboration and less than optimal.